Interaction between statins and clopidogrel: is there anything clinically relevant? - Bhindi, R; Ormerod, O; Newton, J; Banning, A; Testa, L (2008)
Since their introduction several years ago, the 3-hydroxy-3-methylglutaryl coenzyme A (HMGCoA) reductase inhibitors-the statins-have been widely used for hyperlipidemia and for the primary/secondary prevention of cardiovascular diseases. They have been shown to be safe as well as efficacious in a number of different clinical trials; however, studies have suggested that they can interact with other co-administered therapies. More recently, the thienopyridines have been successfully integrated with the conventional medical treatment of coronary disease as they showed effectiveness in reducing platelet activity both in stable and unstable settings. They also improve the outcome of patients treated with percutaneous coronary intervention. The potential interaction of statins and thienopyridines is a matter of concern. Despite some preclinical data suggesting an interaction between statins metabolized by the liver cytochrome P3A4-such as atorvastatin, lovastatin and simvastatin-and clopidogrel, there is no compelling clinical evidence to stop their co-administration.